Faktor-Faktor Makroekonomi yang Mempengaruhi Investasi Asing pada Sektor Industri, Perdagangan dan Pertanian di Jawa Timur - Dauty Fitri Suryaningtyas (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2018)
The purpose of this study was to analyze several macroeconomic factors that influence sectoral investment development in East Java through secondary data obtained from BPS East Java over a 10-year period with multiple linear regression analysis tools with the Statistical Program for Social Science version 13. Results Simultaneous analysis of independent variables significantly affects the dependent variable. Whereas from partial testing of Foreign Exchange Rate-free variables significantly affect the FDI of the Industrial Sector and PMA in the Trade Sector this is because the exchange rate can affect investment. The independent variable of Economic Growth and Inflation has no partial effect on Industrial Sector FDI and Trade Sector PMA. For Foreign Investment in the Agricultural Sector there is no independent variable in the partial test that affects the dependent variable because the agricultural sector is not the main choice of investors to invest.